2019
DOI: 10.31643/2019/6445.37
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of plasticizers and thermoplastics on the mechanical properties of epoxy and carbon fiber reinforced plastic (Review)

Abstract: Аннотация. Задача создания технологии упрочнения эпоксидной смолы (ЭС) и углепластика актуальна для многих разделов техники: космической, авиационной, оборонной, автомобильной и др. Вопрос решается многочисленными приемами модификации ЭС, компонентов углепластика. Модификация ЭС осуществляется путем ввода различных химических соединений. Одним из методов упрочнения углепластика является модификация пластификаторами (трикрезилфосфат, олеиновая кислота) или термопластами (полисульфон, поликарбонат, полистирол, у… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The increase is due to the functional groups of the modifier that react with one of the components of the curing system. 8,20 In the case of ER modification with TCP plasticizer, the increase in TCP share leads to a decrease in strength properties of the composite. It was observed that the tensile and bending strength decreases as TCP content increases from 10 to 20 % wt., while there is a decrease and increase in bending strength.…”
Section: Research On Ways To Improve the Mechanical Properties Of Org...mentioning
confidence: 99%
See 1 more Smart Citation
“…The increase is due to the functional groups of the modifier that react with one of the components of the curing system. 8,20 In the case of ER modification with TCP plasticizer, the increase in TCP share leads to a decrease in strength properties of the composite. It was observed that the tensile and bending strength decreases as TCP content increases from 10 to 20 % wt., while there is a decrease and increase in bending strength.…”
Section: Research On Ways To Improve the Mechanical Properties Of Org...mentioning
confidence: 99%
“…As it is known, the mechanical properties of AF/ERs depend not only on the strength properties of the fibers and matrix, but also on the nature of the fiber surface and the mechanisms of load transfer from matrix to fiber at the interface. 7 Therefore, modern literature reports quite a lot of studies [8][9][10][11] on ways to improve the mechanical characteristics of AF/ERs and currently there is a search for optimal technologies. For example, they can consist of modifying the polymer matrix, various treatments of the fiber reinforcement, combination of reinforcement, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Various plasticizers or thermoplastics are most often used [6] as modifiers of epoxy resins. Oleic acid, oligoxypropylene glycol and dchlorobutyl esterβchloropropionic acid were studied in the work [7] as the plasticizers for ED20 epoxy resin on a polyethylene polyamine (PEPA) hardener.…”
mentioning
confidence: 99%
“…From the works [6][7][8]10], it follows that the modification of epoxy resin with plasticizers and thermoplastics is promis ing both for increasing the toughness and strength of the com posite. However, these works deal mainly with the widely used ED20 "cold" hardening epoxy.…”
mentioning
confidence: 99%
See 1 more Smart Citation